Crystal structure and optical properties of 1,6-bis(methylthio)pyrene, C18H14S2 - Wang Guang-Qing (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C18H14S2, monoclinic, P21/c (no. 14), a = 10.196(3) Å, b = 14.756(4) Å, c = 9.508(3) Å, β = 103.965(14)°, V = 1388.3(7) Å3, Z = 4, Rgt(F) = 0.0480, wRref(F2) = 0.1207, T = 200(2) K.